Genetic testing when there is a mix of public and private health insurance - Michael Hoel; Tor Iversen (University of Oslo, Department of Economics, 2000)
Genetic insurance can deal with the negative effects of genetic testing on insurance coverage and income distribution when the insurer has access to information about test status. Hence, efficient testing is promoted. When information about prevention and test status is private, two types of social inefficiencies may occur; genetic testing may not be done when it is socially efficient and genetic testing may be done although it is socially inefficient. The first type of inefficiency is shown to be likely for consumers with public insurance only, while the second type of inefficiency is likely for those with a mix of public/private insurance. This second type of inefficiency is more important the less effective prevention is. It is therefore a puzzle that most countries have placed some kind of restrictions on what type of health information insurance companies have access to.
Keywords: D82; H52; I18; 330; Genetic testing; insurance; private information; public/private mix; Gentechnik; Gesetzliche Krankenversicherung; Private Krankenversicherung; Asymmetrische Information; Theorie